Molecular and morphological evidence support four new species in the genus Muscodor from northern Thailand - Nakarin Suwannarach (2018)
The genus Muscodor comprises fungal endophytes which produce mixtures of volatile compounds (VOCs) with antimicrobial activities. In the present study, four novel species, Muscodor musae, M. oryzae, M. suthepensis and M. equiseti were isolated from Musa acuminata, Oryza rufipogon, Cinnamomum bejolghota and Equisetum debile, respectively; these are medicinal plants of northern Thailand. The new Muscodor species are distinguished based on morphological and physiological characteristics and on molecular analysis of ITS-rDNA. Volatile compound analysis showed that 2-methylpropanoic acid was the main VOCs produced by M. musae, M. suthepensis and M. equiseti. The mixed volatiles from each fungus showed in vitro antimicrobial activity. Muscodor suthepensis had the highest antifungal activity. © Springer-Verlag Berlin Heidelberg and the University of Milan 2013.